2020
DOI: 10.3390/microorganisms8010083
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with Rhizophagus irregularis Does Not Alter Arbuscular Mycorrhizal Fungal Community Structure within the Roots of Corn, Wheat, and Soybean Crops

Abstract: Little is known about establishment success of the arbuscular mycorrhizal fungal (AMF) inocula and their effects on a soil-indigenous community of AMF. In this study, we assessed the effect of introducing Rhizophagus irregularis DAOM-197198 in soil under field condition on the community composition of indigenous AMF in the roots of corn (Zea mays), soybean (Glycine max), and wheat (Triticum aestivum). Three field trials were conducted with inoculated and non-inoculated plots. Four to ten roots and their rhizos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…These results agree with data recorded at tillering and anthesis in field-grown bread wheat inoculated with R. irregularis [as G. intraradices] or with an AMF polispecies inoculum [56][57][58]. Conversely, at physiological maturity, similarly to the results of Renaut et al [59], root colonization was no longer affected by AMF inoculation, indicating that at this stage, the system became saturated (independent from initial infectious propagules concentration, including native ones).…”
Section: Amf Root Colonizationsupporting
confidence: 90%
See 1 more Smart Citation
“…These results agree with data recorded at tillering and anthesis in field-grown bread wheat inoculated with R. irregularis [as G. intraradices] or with an AMF polispecies inoculum [56][57][58]. Conversely, at physiological maturity, similarly to the results of Renaut et al [59], root colonization was no longer affected by AMF inoculation, indicating that at this stage, the system became saturated (independent from initial infectious propagules concentration, including native ones).…”
Section: Amf Root Colonizationsupporting
confidence: 90%
“…Previous works, tracing the SSU RNA gene, the internal transcriber spacer 2 (ITS2) and the large subunit (LSU), successfully discriminated between inoculated and native isolates, and found in Medicago sativa the inoculated Funneliformis isolates AZ225C and IMA1 at early crop growth stages, whereas two years after inoculation only AZ225C was retrieved [42]. Other authors did not detect, using the mtLSU marker, the inoculated AMF isolates [59] or could only detect minor effects in several crops [100]. The failure of detection of the inoculant might be due to the specificity of the markers or to the complex factors affecting field AMF inoculation, such as viability/infectivity of the inoculated isolates or incompatibilities with soil or host crop [101,102].…”
Section: Arbuscular Mycorrhizal Fungal Community Diversitymentioning
confidence: 96%
“…The isolated DNA was then diluted tenfold in Milli-Q type 1 sterile water to reduce the risk of PCR inhibition by PH contaminants and humic substances. A two-step nested PCR was performed in order to amplify part of the 18S rRNA gene of arbuscular mycorrhizal fungi using primers AML1 (5 -ATCAACTTTCGATGGTAGGATAGA-3 ) and AML2 (5 -GAACCCAAAC ACTTTGGTTTCC-3 ) according to Lee et al [40] for the first step, followed by an in-house set of internal primers: nu-SSU-0595-5' CGGTAATTCCAGCTCCAATAG / nu-SSU-0948-3' TTGATTAATGA AAACATCCTTGGC with overhang adapter sequences to produce a final amplicon size of~400 bp [41]. Finally, Illumina Miseq-specific indexes were attached to the generated amplicons using the Nextera XT V2 kit using a limited-cycles PCR as recommended by the manufacturer.…”
Section: Dna Extraction Pcr Amplification and Illumina Miseq Sequencingmentioning
confidence: 99%
“…Therefore, for AMF inoculant industry to thrive, rigorous research must be conducted to provide best practices to the inoculant companies regarding composition, quality, quantity, and application methods of the products [ 19 ]. Although lack of efficacy or negative impacts of AMF inoculation has been reported [ 20 , 21 , 22 ], recent studies conducted under field conditions have shown promising results [ 12 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%